Molecular detection of Mycobacterium tuberculosis in formalin-fixed, paraffin-embedded tissues and biopsies of gastrointestinal specimens using real-time polymerase chain reaction system - Pradyumna Kumar MISHRA; Venkata Raghuram GORANTLA; Arpit BHARGAVA; Subodh VARSHNEY; Purushottam VASHISTHA; Kewal Krishan MAUDAR (Turkish Journal of Gastroenterology, 2019)
-